Enhanced photocatalytic degradation rate of 2, 4-dichlorophenol by P25 in Na2CO3/NaHCO3 buffer solution. Issue 181 (13th June 2017) - Zhang, Wei; Peng, Zhi; Sun, Jin; Wang, Lei; Zhao, Xiaoliang; Yang, Chao
ABSTRACT: The degradation of 2, 4-dichlorophenol (2, 4-DCP) in wastewater is widely concerned in recent years because of its toxicity, carcinogenic and mutagenic properties. Generally, the pH values vary during the process of photocatalytic degradation, effecting UV-Vis absorbance spectral of 2, 4-DCP. In this paper, we utilized the Na2 CO3 -NaHCO3 buffer solution to eliminate the impact of pH changes caused by the acidic intermediates. As a result, the removal efficiency of 2, 4-DCP and the reaction rate are significantly elevated. It can be concluded that the buffer solution can promote the photocatalytic degradation of 2, 4-DCP effectively.